The Impact of Indonesian Language Module Utilization on the Vocabulary Acquisition Skills of Students at Serang Raya University - Lina Marliana Dewi; Wahyuddin Wahyuddin; Ratu Erlina Gentari (International Journal of Science and Environment (IJSE), 2025)
This study investigated the impact of Indonesian language module utilization on vocabulary acquisition and speaking skills among Management Class A2 students at Serang Raya University, motivated by observed challenges in their verbal expression and communication benchmarks. Recognizing language's fundamental role in national development and effective communication, the research specifically aimed to ascertain the modules' influence on students' vocabulary acquisition. Utilizing a quantitative descriptive and correlational design, data were collected from 21 Management Class A2 students through Google Forms questionnaires, classroom observations, semi-structured interviews, and documentation analysis. The study assessed student perceptions of the Indonesian language module's effectiveness in improving vocabulary, its application, retention, and impact on writing skills, noting a majority of students actively used the module over extended periods. The study's findings unequivocally demonstrate a significant positive influence of Indonesian language modules on students' vocabulary acquisition. A robust correlation was established, indicating that enhanced vocabulary mastery directly improves speaking abilities and fosters more active learning participation. Quantitative analysis of questionnaire results, yielding an 18.97% score, categorized the module as "Very Helpful," thereby strongly supporting its perceived effectiveness. This direct correlation between higher vocabulary and more responsive speaking facilitates improved lecturer-student communication and overall academic engagement. Consequently, the study concludes that Indonesian language modules are highly effective in developing students' vocabulary, which in turn significantly boosts their speaking proficiency and academic communication, underscoring their critical role in fostering essential linguistic competencies for personal growth and national development.